Analysis of the concentration in the production of electricity after liberalization in Spain Electricity Sector (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This paper is about the Spanish Electricity Market after liberalisation. The analysis focuses on finding if the market has become as a Perfect Competition regimen or on the other side, he still continues as a regimen in wich a high output supply concentration and high power market appears, not allowing free-market prices as a consequence. Regarding on it, CTC s are especially important, being responsible of voluntary actions of increasing prices by Electricity Companies with high market power,just trying to maximise incomes illegally.
Keywords: Liberalization; electricity output; competition and market power; Industry Concentration Indexes; energy prices; Competence Transition Costs.